2022
DOI: 10.1128/aac.01744-21
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Empirical Antibiotic Regimens on Mortality in Neutropenic Patients with Bloodstream Infection Presenting with Septic Shock

Abstract: Objectives: We analyzed risk factors for mortality in febrile neutropenic patients with bloodstream infections (BSI) presenting with septic shock and assessed the impact of empirical antibiotic regimens. Methods: Multicenter retrospective study (2010-2019) of two prospective cohorts comparing BSI episodes in patients with or without septic shock. Multivariate analysis was performed to identify independent risk factors for mortality in episodes with sept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 38 publications
0
20
0
1
Order By: Relevance
“…Many studies have focused on assessing the impact on mortality of an inadequate empirical antimicrobial treatment not only in specific scenarios, like the intensive care units (ICU) (Alvarez-Lerma; Ibrahim et al; Kollef et al; Luna et al; Rello et al; Kreger et al, 1980; Savage et al, 2016 ) but also it has been analysed in a broad spectrum of infections ( Mettler et al, 2007 ; Paul et al, 2010 ). Concretely in patients with bacteremia, inadequate therapy has demonstrated to negatively impact on mortality in specific populations like oncohematological patients with febrile neutropenia ( Martinez-Nadal et al, 2020 ; Chumbita et al, 2022 ) or cirrhotic patients ( Park, 2015 ). Also, results from a very recent meta-analysis indicated that i-EAT substantially had a negative impact on survival of patients with BSIs at short and long term ( Hung et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have focused on assessing the impact on mortality of an inadequate empirical antimicrobial treatment not only in specific scenarios, like the intensive care units (ICU) (Alvarez-Lerma; Ibrahim et al; Kollef et al; Luna et al; Rello et al; Kreger et al, 1980; Savage et al, 2016 ) but also it has been analysed in a broad spectrum of infections ( Mettler et al, 2007 ; Paul et al, 2010 ). Concretely in patients with bacteremia, inadequate therapy has demonstrated to negatively impact on mortality in specific populations like oncohematological patients with febrile neutropenia ( Martinez-Nadal et al, 2020 ; Chumbita et al, 2022 ) or cirrhotic patients ( Park, 2015 ). Also, results from a very recent meta-analysis indicated that i-EAT substantially had a negative impact on survival of patients with BSIs at short and long term ( Hung et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite of the relevance of choosing i-EAT, there is much less evidence on the risk factors associated with this practice. Some studies have focused on concrete patient-related factors ( McDonald et al, 2005 ; Retamar et al, 2013 ) while others have analysed heterogeneous clinical syndromes ( Mettler et al, 2007 ), have small sample size ( Bai et al, 2021 ) or have focused on specific populations like neonates ( Hsu et al, 2015 ) or immunosuppressed patients ( Martinez-Nadal et al, 2020 ; Chumbita et al, 2022 ), which makes their findings ungeneralizable to general adult population. More recently, some studies have focused on the impact of isolation of multidrug resistant (MDR) strains on the adequation of empirical antimicrobial treatment choice ( Girometti et al, 2014 ; Carrara et al, 2018 ) showing higher rates of i-EAT when a MDR microorganism was identified and thus, a negative impact on mortality.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we also found that septic shock was the predominant and significant predictor for 28-day mortality in our nomogram. Not surprisingly, septic shock, as a clinical manifestation of the severity of infections and organ dysfunction, has been detected to be associated with high mortality in several previous studies involving patients with HM and the general populations ( Andria et al., 2015 ; Chumbita et al., 2022 ; Xiao et al., 2020 ; Zhang et al, 2020 ). In the current study, we could understand that 60.3% (41/68) of non-survivors underwent septic shock, of which 50.9% (27/53) of patients were categorized as CR-GNB BSI.…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, in clinical practice, the severity of the infection plays a crucial role in the prognosis. As demonstrated by Chumbita et al, (2022), when administered with inappropriate experimental antibiotic therapy, septic shock was associated with extremely high mortality in febrile neutropenic patients with BSI. Apparently, this conclusion further highlights the importance of epidemiological surveillance in different hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…As delay reduces the effectiveness of antibiotherapy, so does the prescription of antibiotics that are not active against the pathogens causing the infection [13]. Surprisingly, in our current clinical practice, the rate of prescribing empirical antibiotic therapy that is inactive or ineffective is very high (up to 20 and 30%) [13][14][15][16][17][18]. And the rate would be even worse assuming this new strategic concept that appears in recent leading publications: that in severe infections caused by multidrug-resistant bacteria, two active antibiotics improve the survival rate over that achieved with monotherapy [16, [19][20][21].…”
Section: Introductionmentioning
confidence: 99%